PATHOGENICITY AND CHEMOTHERAPY OF GYFODACTYLUS NEONEPHROTUS MALMBERGI SINGH AND AGRAWAL, 1994 - SINGH, H.S.; AGRAWAL, SHILPI; KUMAR, KAPIL; SHARMA, BINDU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
Present communication deals with the pathogenicity and chemotherapy of a freshwater viviparous monogenean, G. neonephrotus malmbergi Singh and Agrawal, 1994.